2020
DOI: 10.1108/pr-02-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Perceived organizational support and work engagement of employees with children with disabilities

Abstract: PurposeThe purpose of this research is to investigate the role of organizational support, as it is evidenced by supervisor's support and coworkers' support, in the work engagement levels of employees who are parents of children with special needs and disabilities (SND).Design/methodology/approachThe authors employed a self-administered survey questionnaire in Singapore and collected 224 useable responses. They used moderated hierarchical regression analysis to assess the relationships among organizational supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 81 publications
(126 reference statements)
2
17
0
2
Order By: Relevance
“…Such support from the organisation would lead to positive consequences on employees' behaviours, e.g., increased organisational commitment, job satisfaction and reduced turnover, among others (Rhoades and Eisenberger, 2002;Bentley et al, 2016). Moreover, organisational support can be viewed as a guarantee that the appropriate support will be available to employees when they need to execute a particular duty and to handle challenges (Stefanidis and Strogilos, 2020). Therefore, it can be claimed that employees may see that their favourable actions will encourage their organisations to demonstrate support in return for their treatment (Tang et al, 2017).…”
Section: Perceived Organisational Supportmentioning
confidence: 99%
“…Such support from the organisation would lead to positive consequences on employees' behaviours, e.g., increased organisational commitment, job satisfaction and reduced turnover, among others (Rhoades and Eisenberger, 2002;Bentley et al, 2016). Moreover, organisational support can be viewed as a guarantee that the appropriate support will be available to employees when they need to execute a particular duty and to handle challenges (Stefanidis and Strogilos, 2020). Therefore, it can be claimed that employees may see that their favourable actions will encourage their organisations to demonstrate support in return for their treatment (Tang et al, 2017).…”
Section: Perceived Organisational Supportmentioning
confidence: 99%
“…Dari penelitian terdahulu telah membuktikan bahwa digital intelligence quotient memberi kontribusi teoritis untuk meningkatkan employee understanding (Na-Nan et al, 2019). Dari studi empiris lainnya juga dapat dibuktikan bahwa terdapat hubungan positif antara variabel authentic leadership dengan work engagement menurut (Plessis dan Boshoff, 2018) serta terdapat pengaruh antara perceived organizational support terhadap work engagement (Stefanidis & Strogilos, 2021).…”
Section: Work Engagementunclassified
“…Previous research has disclosed the correlation between the quality of relation of employees with their immediate manager and their engagement at work and so many organizations are emphasizing on building relation of trust between managers and employees (Purse, 2015). In case of employee with children, support from co-workers and supervisors leads to increase in their engagement levels at work (Stefanidis and Strogilos, 2020). Previous research has also shown the correlation of trust between supervisors and subordinate and OCB (Podsakoff et al , 1990; Deluga, 1994).…”
Section: Theoretical Groundingsmentioning
confidence: 99%
“…Similarly Bakker and Demerouti (2007) claimed that the JD-R model also shows that the presence of higher job resources increases the engagement level. Stefanidis and Strogilos (2020) have demonstrated in the case of employees with children who require special care that support from supervisor and co-workers enhances their engagement. We extend these concepts by proposing that three trusts mediate the relationship between organizational culture and employee engagement.…”
Section: Theoretical Groundingsmentioning
confidence: 99%